The interdependence of ESP and pragmatics: a study of BEL315 documents as used in UiTM Terengganu / Elangkeeran Sabapathy, Chittra Muthusamy and Rasaya Marimuthu - Sabapathy, Elangkeeran; Muthusamy, Chittra; Marimuthu, Rasaya (2007)
The purpose of this study is to explore the possibility of incorporating Pragmatics as a component of ESP courses. For this purpose, one ESP course designed for Accountancy students, BEL 315 as taught in UiTM Terengganu, has been chosen as the platform for testing the suitability of Pragmatics tenets. This study attempts to focus its attention on only document analysis. Although the scope is limited, it is to be the starting point for more dynamic studies in line with the idea that Pragmatics should be taught to students of ESP as a tool (means) to enable them to face real-life situations at the workplace. The documents looked into are the syllabus/the course outline, the prescribed textbook, a sample examination paper and the marking scheme that accompanied it. The findings are in the form of discussions on the marked affinity/ interdependence of course material with the tenets of Pragmatics. Due to the present notion of examination driven ESP courses, this study is hoped to be an eye-opener to Lecturers, course designers and curriculum developers, as to the main purpose in providing ESP courses in the first place. The students’ ability to score well in examinations does not always translate as their ability to come unscathed in real-life meaningful interactions. With the inclusion of Pragmatics in ESP courses, it is hoped that students’ can equip themselves with the means and the platform for lifelong learning by having the ability to adapt and behave according to dynamic situations. By the findings of this study, the researchers would like to state that Pragmatics which is inherent in ESP courses should be exploited fully by having them taught explicitly and in a theory informed manner so the students will be aware not only of their existence but will be able to utilize them as is what will be the primary purpose of ESP courses.